The Ecological intelligence as alternative to environmental contamination - Fernández-Dávila, Marli Judit (2023)
The present work was elaborated based on a review of books and articles on Ecological Intelligence as a psychological tool that could develop in the individual, the capacity to modify his consumerist behavior and adopt an ethical responsibility towards environmental pollution that is damaging the physical and mental health of all people; through the change of beliefs and awareness of the harmful effects generated by each phase of industrial production. Those psychological barriers of inaction in the face of climate change are identified, among them; the lack of methods to curb environmental pollution, limiting ideologies, the influence of the masses that promote consumerism, fear of change, the financial losses that ecological production represents and the inadequate application of awareness campaigns, all of them denominated as "Dragons of Inaction" that prevent the development of pro-environmental skills. Finally, the ABC model of Rational Emotive Behavioral Therapy (REBT) by Albert Ellis is recommended as an alternative to face the ecological crisis; so that, with the modification of irrational beliefs about the environment, a pro-environmental behavior can be provoked in the population. All this, through the application of group intervention programs at educational and social level, with philosophical, empirical, pragmatic debates, which promote prosocial attitudes to safeguard the welfare of the person through the care of nature